(untitled) (Acta Scientiarum. Biological Sciences, 2022)
In vitro oxidation is a problem for some herbaceous and woody species and can cause darkening of tissues and consequently death of explants and plants Therefore, this study aimed to assess the effect of activated charcoal on in vitro yam cultivation, aiming at reducing or eliminating explant oxidation and optimizing the growth of the genotypes Dioscorea alata var. purpurea (Roxb.) A. Pouchet and Dioscorea rotundata Poir. Nodal segments of approximately 1 cm, extracted from plants previously grown in vitro, were introduced into test tubes containing 10 mL of 2GGC culture medium, plus 30 g L-1 sucrose, solidified with 2.2 g L-1 Phytagel® and pH adjusted to 5.8 before autoclaving, containing activated charcoal doses of 0, 1, 2, 3 and 4 g L-1. Plants were maintained for 90 days in a growth room, with temperature of 27 ± 1ºC, photon flux density of 30 Î¼mol m-2 s-1 and photoperiod of 16 hours, after which their development variables were evaluated. Activated charcoal, at the concentration of 4 g L-1 considerably promoted the best development of plants, and the species D. alata var. purpurea showed higher means for all variables studied.